EFFECTS OF PROMOTION PRACTICES ON EMPLOYEE PERFORMANCE IN THE NATIONAL BANK OF KENYA. - Nyaga, Ann W; Omuya, Jacqueline (International Journal of Business, Economics, and Social Development, 2024)
Recruitment is a fundamental function in an organization's human resource management department. Its goal is to attract more qualified candidates for potential employment. The adoption of effective recruitment methods by organizations will increase their ability to recruit competent employees with the necessary skills, thereby helping them master their roles. The purpose of this research was to assess the effect of promotion practices on employee performance in the National Bank of Kenya Limited. The following theories underpinned the study; Cattell’s 16PF Trait Theory, Expectancy Theory and Equity Theory. This study employed a descriptive survey design with a target population of 215 members of staff consisting of managers, supervisors and, Bank officers from the Human resource department, Operations department, Marketing department and Finance department of the National Bank of Kenya, head office. Various departments were chosen using both stratified sampling and simple random sampling methods, based on their employee levels.  A sample comprising 144 respondents was utilized for data collection using a questionnaire and an interview guide for the head of personnel service. Quantitative information obtained was edited, coded and analyzed. Data was analyzed using the Statistical Package for Social Science (SPSS). Both descriptive and inferential statistics were utilized in this study with the results given in tables and figures. The study found that promotion practices had positive statistically significant influence on employee performance in the NBK. On promotion practices, the study concluded that the bank has a promotion policy for employees and that promotion is accorded to employees based on merit.